2018
DOI: 10.1159/000488238
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis: An Efficacious and Well-Tolerated Treatment for Cutaneous and Oral Mucosal Chronic Graft-versus-Host Disease

Abstract: Background: Extracorporeal photopheresis (ECP) is a second-line therapy for steroid-refractory chronic graft-versus-host disease (cGVHD). Objective: We describe the long-term efficacy and tolerability of ECP according to the cutaneous phenotype of cGVHD and report on the reduced need for immunosuppressant drugs in this setting. Patients and Methods: Fourteen patients (8 females) with cutaneous and/or mucosal cGVHD, treated with ECP between October 2010 and May 2016 within a single center, were included. Final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We found previous studies where authors treated patients with just one ECP procedure (Table ) . Authors using inline ECP procedures collected MNCs after processing 1500 mL of whole blood . However, Garban and colleagues collected MNCs with an offline system after processing “three whole blood masses” and Iniesta and coworkers did not mention the quantity of whole blood processed in their study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We found previous studies where authors treated patients with just one ECP procedure (Table ) . Authors using inline ECP procedures collected MNCs after processing 1500 mL of whole blood . However, Garban and colleagues collected MNCs with an offline system after processing “three whole blood masses” and Iniesta and coworkers did not mention the quantity of whole blood processed in their study.…”
Section: Discussionmentioning
confidence: 93%
“…[24][25][26][27][28][29][30][31][32] Authors using inline ECP procedures collected MNCs after processing 1500 mL of whole blood. [25][26][27][28][30][31][32] However, Garban and colleagues 24 collected MNCs with an offline system after processing "three whole blood masses" and Iniesta and coworkers 29 did not mention the quantity of whole blood processed in their study. After all the previous studies were reviewed, it is obvious that there is no consensus regarding the most appropriate ECP schedule for treating patients with acute or chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Another second-line therapy that is used in conjunction with immunosuppressives is extracorporeal photopheresis (ECP), especially in the cutaneous and mucosal manifestations, 59 ECP may also be useful in as a first-line therapy in patients that have contraindications to immunosuppressives such as cerebral toxoplasmosis. 60 While the mode of action is unclear, the combination of leukapheresis and photodynamic therapy has been reported to help to moderate the effects of GVHD. A multicenter trial, with results reported in 2018, showed that ECP had a 62% provider response rate and a 44% NIH criteria response rate.…”
Section: Overview Of Cgvhdmentioning
confidence: 99%